2015
DOI: 10.1371/journal.pone.0135381
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Diversity of Photoreceptor Classes in the Longfin Squid, Doryteuthis pealeii

Abstract: Cephalopods are famous for their ability to change color and pattern rapidly for signaling and camouflage. They have keen eyes and remarkable vision, made possible by photoreceptors in their retinas. External to the eyes, photoreceptors also exist in parolfactory vesicles and some light organs, where they function using a rhodopsin protein that is identical to that expressed in the retina. Furthermore, dermal chromatophore organs contain rhodopsin and other components of phototransduction (including retinochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Right: Morphological key for the cephalopod eye, showing the rhabdoms (r), proximal region/supporting cell layer (p/s), inner segments (is), photoreceptor nuclei (n), and plexiform layer (pl). For comparative labeling in the eye, es-rhodopsin expression occurred at the extreme ends of the rhabdoms similar to the protein localization in another squid species ( Doryteuthis pealeii ; Kingston et al 2015), but also extended into the inner segments. Labeling of es-crumbs occurred within the inner segments.…”
Section: Figurementioning
confidence: 73%
See 1 more Smart Citation
“…Right: Morphological key for the cephalopod eye, showing the rhabdoms (r), proximal region/supporting cell layer (p/s), inner segments (is), photoreceptor nuclei (n), and plexiform layer (pl). For comparative labeling in the eye, es-rhodopsin expression occurred at the extreme ends of the rhabdoms similar to the protein localization in another squid species ( Doryteuthis pealeii ; Kingston et al 2015), but also extended into the inner segments. Labeling of es-crumbs occurred within the inner segments.…”
Section: Figurementioning
confidence: 73%
“…As a complementary experiment, we examined histological samples of the light organ and eye using paraffin-section ISH methods as previously described (Peyer et al 2014). In the eye, we localized es-crumbs along with es-rhodopsin to confirm that both genes occur in regions of the photoreceptors similar to other animals (Kingston et al 2015; Hsu and Jensen 2010). We included rhodopsin because it is a common reference gene in the eye.…”
Section: Methodsmentioning
confidence: 80%
“…Not only are rhodopsin and retinochrome important for the cephalopod visual system, they are also found together in extraocular tissues serving a potential role in camouflage (Kingston et al 2015). By adding a squid retinochrome sequence to our opsin phylogeny we found that the lepidopteran-specific unclassified opsin and RGR-like opsin are more closely-related to retinochrome than they are to other opsins with known functions ( Figure 4A).…”
Section: Opsins In Lepidopteramentioning
confidence: 97%
“…The recently published octopus genome (22) did not identify any additional opsins using both whole-genome sequencing and transcriptome sequencing of skin tissue, despite a focus on identifying G protein-coupled receptors. Across a diversity of taxa, all cephalopod studies to date have found rhodopsin transcripts in the skin identical to those in the eye (23), and the skin's spectral response to light is nearly identical to that of the retina (24). Given multiple strong lines of evidence against additional undiscovered skin opsins and no described mechanism for spectral discrimination arising from rhodopsin alone, this competing hypothesis is not currently viable.…”
Section: Contradictory Evidence: Chromatic Behavior But a Single Opsinmentioning
confidence: 99%